PEMETAAN DOMAIN COBIT 5 DALAM TATA KELOLA TI PENERAPAN OFFICE 365 DI ITB STIKOM BALI - Ni Made Rai Masita Dewi; Dian Pramana; Odie Kharisma Putra (Universitas PGRI Yogyakarta, 2021)
The application of IT in the world of education is the use of Office 365, this application is one of the supporters of the learning process, especially the implementation of a learning system from home, ITB STIKOM Bali collaborates with Microsoft, one of which is the use of office 365 applications for the academic community. ITB STIKOM Bali is a university that carries out IT governance, the university is responsible for managing information within the academic community. Office 365 has an important role in infrastructure development at ITB STIKOM Bali. Therefore, the management process must be carried out properly, to determine the level of maturity in the use of office 365. The use of office 365 still needs to be measured to find out the problems that occur in the field. Before measuring IT Governance, the first step that must be done is Process mapping. Mapping is done to find out what process will be used in making measurements. The survey was carried out by applying the COBIT 5 framework by applying the Process Assessment Model, adapted to the conditions in which the research was conducted. The tuning process is carried out from the COBIT 5 domain.